Communities of practice through intercultural telecollaboration - Castro-Prieto, Paloma; Salomão, Ana Cristina Biondo [UNESP]; Derivry-Plard, Martine; Fan, Sa-Hui (IGI Global, 2022)
Communities of practice provide challenging learning opportunities based on the principles of interaction, participation, dialogue, and relationship building. This chapter aims to explore how intercultural telecollaboration contributes to the development of a multicultural community of practice in the context of initial teacher education. Four groups of student teachers from four different languages and cultures- two in Europe, one in Asia, and one in South America-work together through the medium of English in an intercultural telecollaboration project. The project is examined in terms of community building through the experience journal of the student teachers as a reflective narrative on how they built a sense of community to sustain their interactions and negotiation of meaning. The findings strongly suggest that intercultural telecollaboration creates a powerful learning environment where students and teachers can find opportunities to cooperate, understand and support each other, and enhance their perceptions of teaching English from an intercultural perspective.